Molecular investigation into brachydactyly type A1 - McCready, Mary Elizabeth (University of Ottawa (Canada), 2004)
Brachydactyly type A1 (BDA1) is a rare, autosomal-dominant genetic trait that affects normal limb and bone development, resulting in short or absent middle halan es. Despite being the first human trait described in terms of autosomal dominant Mendelian inheritance, the underlying molecular cause had not been examined until relatively recently. In 2001, mutations of the Indian Hedgehog (IHH) gene were identified in three Chinese families with BDA1. Preliminary studies in our laboratory further demonstrated linkage of BDA1 to chromosome 5p in a Canadian kindred with a mild variant of the trait. The goal of this thesis was to characterize the BDA1 locus on chromosome 5 by reducing the critical region and examining the transcribed portions of candidate genes for mutations. To reduce the chromosome 5p critical region in the Canadian kindred, 23 microsatellite markers were examined and the number of family members analyzed was increased to include 22 affected and 16 unaffected individuals. By doing so, we defined a 7 cM (3.03 Mb) critical region flanked by the recombinant markers D5S1986 and D5S426. Fifteen candidate genes within the region were examined for mutations, however none were identified. Further characterization of the chromosome 5p critical region was made by recruiting twelve additional families into the study. Of the twelve families, five had a G → A transition at codon 100 of the IHH gene. The mutation causes an aspartate to asparagine amino acid substitution and supports a role for IHH in normal bone development. Linkage analysis to chromosome 5 in two other pedigrees indicated that the trait was not linked to this locus in these families, and provided further support for genetic heterogeneity underlying the aetiology of BDA1. IHH mutations were not found in the remaining five families, thus increasing the likelihood that the chromosome 5 locus is involved in these pedigrees. Linkage could not be established in these families, however, since the trait was sporadic, and not familial. Identification of additional BDA1 families in which the trait is linked to chromosome 5, and further mutational analysis will be required to identify the gene from chromosome 5p that causes BDA1.
Keywords: Biology, Genetics.